UTERINE INVOLUTION IN DAWANESSE POSTPARTUM MOTHERS WITH TATOBI PRACTICES - Kristiani Desimina Tauho; Rifatolistia Tampubolon; Maya Miranthi Oematan (Nurse and Health: Jurnal Keperawatan, 2023)
Background: The Dawan tribe is a tribe on the mainland of Timor Island that owns a tradition of caring for postpartum mothers called Tatobi. Tatobi is a tradition done by compressing the vagina, perineum, abdomen, and mother's breast using a traditional cloth dipped in hot water. Heat stimulation can cause vasodilation, possibly affecting the process of returning the uterus to its original state, known as uterine involution. Objectives: This study aims to determine differences of uterine involution in postpartum mothers who did and did not practice tatobi. Methods: This quantitative study uses a comparative descriptive study design involving 15 exposed groups and 15 control group people. Determination of respondents using the quota in Binaus Health Center, Kapan Health Center, and Fatumnasi Health Center. Technique data collection using direct lochia observation, measurement of uterine fundus height, and interviews to find out the practice of Tatobi. The data were then analyzed using the paired t-test. Results: The study showed no significant difference in FH of exposed and control groups on the first and third days of postpartum, which showed a p-value of 0.325 and 0.261, respectively. In contrast, there was a significant difference in FH on the seventh day, with a p-value of 0.000 at a 95% confidence level. The results also showed no significant difference in lochia’s volume on the 1st and the third day of postpartum (p-values 0.764 and 0.426, respectively). However, the lochia’s volume differed in the exposed and control groups with a p-value of 0.048). The results of this study could be due to the lax practice of tatobi, which is supported by factors of early mobilization, fulfilment of nutria ents, age, and parity. Conclusion: This research concludes that there is a difference of the process of uterine involution in the exposed group and the control group on the seventh day.